Membangun Karakter Islami: EfektivitaMembangun Karakter Islami: Efektivitas Strategi CTL pada Pembelajaran PAI di Era Digital Madrasah - Husnul Khotimah; Intan Khoirunnisah; Gusmaneli . (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Amidst increasingly massive technological disruption, the challenges of moral degradation and character crisis have become a major urgency in Islamic education. This study aims to test and analyze the effectiveness of the Contextual Teaching and Learning (CTL) strategy in transforming Islamic character values ​​in Islamic Religious Education (PAI) subjects in the digital-era Madrasah (Islamic school) environment. Using a qualitative descriptive approach, this study examines how integrating the realities of students’ digital lives into PAI materials can create a more meaningful learning experience (meaningful learning). The results show that the CTL strategy not only bridges the gap between religious theory and daily practice but also significantly increases student engagement. Through PAI materials in the context of digital ethics, students demonstrated character strengthening in the aspects of honesty, responsibility, and social media etiquette. These findings confirm that an adaptive CTL strategy is an effective pedagogical solution for fortifying Madrasah students’ character against the negative impacts of the flow of information, while simultaneously producing a generation of “Digital Muslims” with high integrity.